How Indigenous and non-Indigenous women look at AIDS: convergences and singularities* - Joseane Barbosa Freire da Silva; Rafaela Gerbasi Nóbrega; Sandra Aparecida de Almeida; Édija Anália Rodrigues de Lima; Ana Cristina de Oliveira e Silva; Jordana de Almeida Nogueira (SciELO, 2020)
Abstract Objective: To analyze the way AIDS is configured in the eyes of Indigenous and non-Indigenous women. Method: A descriptive study implementing a mixed approach, conducted in three indigenous villages and in a surrounding municipality. A semi-structured interview script was used, with identification data and questions related to the disease perception, the way of seeing and feeling AIDS. The corpus was processed by IRaMuTeQ software and analyzed by Descending Hierarchical Classification, Content Analysis and Word Cloud. Results: A total of 164 Potiguara indigenous women and 386 non-Indigenous women participated. Three classes were formed: "AIDS and its repercussions", "Social aspects, spirituality and attributed feelings" and "Transmission modes". There was a better understanding of the etiology, treatment and AIDS transmission modes among non- Indigenous women, while the content mainly surrounds negative elements such as death, fear, sadness and prejudice among Indigenous women. Conclusion: The knowledge produced in interactions were formed according to the social context and gain its own significance. Such considerations may contribute to the direction of strategic HIV/AIDS control policies focusing on ethnic/cultural specificities.